CD4-Blockade Can Induce Protection from Peanut-Induced Anaphylaxis - Duarte, Joana; Caridade, Marta; Graca, Luis (Frontiers in Immunology, 2011)
Monoclonal antibodies (mAb) have been shown effective in inducing immune tolerance in a range of animal models of autoimmunity, allergy, and transplantation. We investigated whether CD4-blockade, effective in inducing transplantation tolerance, could prevent systemic immune responses leading to anaphylaxis. We found that treatment with a non-depleting anti-CD4 mAb could prevent peanut-induced anaphylaxis following subsequent systemic exposure to crude peanut extract (CPE). Furthermore, the effect of CD4-blockade did not interfere with overall immune competence, as anti-CD4 treated mice remained fully competent to respond to unrelated antigens. Protection from anaphylaxis correlated with increased frequency of Foxp3+ regulatory T cells (Treg), and was abrogated following Treg depletion. Taken together our data suggest that activation of T cells by CPE in presence of CD4 blockade leads to Treg expansion that can prevent peanut-induced anaphylaxis.